Aproveitamento de resíduos do processamento de uva para a biossorção de corantes e prata - Vanni, Gabriel (2017)
In this work, the potential of wine industry wastes as alternative biosorbents to remove Brilliant Blue (BB) and Amaranth Red (AR) dyes as also Ag ions from aqueous media was investigated; all experiments were performed in batch systems. The wastes were pulverized and sieved until the discrete particles size ranging from 80 to 110 μm and named grape peel (GPE), grape seeds (GSE), and grape stem (GST). These materials were characterized according to the point of zero charge (pHZPC), Boehm titration, Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), energy X–ray dispersive spectroscopy (EDS), and X–ray mapping. In experiments with GSE and dyes, the biosorption was favored at pH 1.0 using biosorbent dosage of 0.500 g L–1, reaching 85% of removal percentage. The pseudo–second order and Elovich models were able to represent the kinetic data, and the Langmuir and Sips models represented the equilibrium. The maximum biosorption capacities were 599.5 and 94.2 mg g–1 for BB and AR, respectively, with spontaneous, favorable and endothermic process. In the experiments with the three biosorbents and silver ions, the biosorption was favored at pH 7.0 using biosorbent dosage of 3.0 g L–1. The kinetic data were well represented by the pseudo–first order model and the equilibrium by the Sips model. The maximum biosorption capacities, found at 298 K, were: 41.7, 61.4, and 46.4 mg g–1 for GPE, GSE, and GST, respectively. The process was spontaneous, favorable, exothermic, and enthalpy–controlled, configuring physical sorption. These results showed that the wine industry wastes can be considered alternative efficient, low–cost, and eco–friendly biosorbents to remove the BB and AR dyes as also Ag ions from aqueous media.